Legal Case Studies on Land and Natural Resource Grabbing in Iceland and Germany - Alexa Abraham 1995- (2024)
Land and natural resources are becoming increasingly scarce. Population growth and environmental changes are placing immense pressure on land and resources to sustain livelihoods and meet food and housing demands. Land and its natural resources are the basis of our livelihood, and they enable economic development and our prosperity. Inadequate management and governance of land and resources play a significant role in their depletion. Furthermore, inequitable distribution of land and resources exacerbates scarcity, leading to social and legal conflicts. The international investment market has long recognized the value in the scarcity of land and natural resources. Large-scale land investments inevitably have consequences for the affected country and its population. If the investment has a negative impact on the country, local population, and human rights, it is referred to as land grabbing. Traditionally associated with developing countries, land and resource grabbing has expanded its reach to industrialized states including Iceland and Germany. Various legal instruments, from the international to the national level can be linked to land and resource grabbing. It turns out that in a globally connected world, international and European legal frameworks are limited in their effectiveness to prevent the negative consequences of land and resource grabbing as shown in the case studies. The lack of consensus on the terminology and the difficult balancing act between the protection of individual land property rights and the fair distribution of land make it difficult to create legal responses. International law on the subject provides certain non-binding legal frameworks and core principles to promote human rights and protect the local population. But ultimately, each individual state is responsible for implementing them and tailoring them to their own needs. National legislation must also consider the limits of European fundamental freedoms, especially the freedom of capital. Each state therefore bears great ...